Novel Deformable Vesicle for the Transdermal Delivery of Terbinafine Hydrochloride-Formulation and Cytotoxic Evaluation - Johl, Shaanya; Bhattacharyya, Sayani (Indian Journal of Pharmaceutical Education and Research, 2024)
Aim/Background: According to estimates, about a billion people in the world have fungal infections of the skin, nails, and hair. Skin disorders are a significant contributor to disability, deformity, and misery among people. In the present study, a versatile vesicular delivery of terbinafine hydrochloride through the dermal route in a biocompatible platform consisting of glycerine, phospholipids, and cholesterol is proposed for the treatment of mycoses. Materials and Methods: The glycerosomes of terbinafine hydrochloride were formulated by thin film hydration technique using central composite design to explore the composition effects on the formation of nanosized stable glycerosomes and drug loading. The optimized formulation was evaluated for deformability, antifungal activity, compatibility by FTIR, surface morphology, in vitro and ex vivo drug diffusion, skin irritation, histopathology, and cytotoxicity studies on HaCaT cell lines. Results: Numerical optimization of the design revealed that the particle size and entrapment efficiency of the drug were remarkably affected by the composition. Surface imaging by TEM revealed the formation of well-defined vesicles with no aggregation. The elasticity of the vesicles was established by determining their deformability index. The in vitro and ex vivo drug release study revealed better permeation of the drug compared to the marketed formulation. The histopathology and cytotoxicity study conceded the suitability of the glycerosomal carrier system for the transdermal delivery of terbinafine hydrochloride. Conclusion: Hence it can be concluded that the glycerosomes of terbinafine hydrochloride possess a potential formulation approach for treating dermal infection.
Keywords: Glycerosomes; Terbinafine hydrochloride; Transdermal delivery; Skin permeation; Cytotoxicity